Altered white matter microstructure associated with mild and moderate depressive symptoms in young adults, a diffusion tensor imaging study. Issue 8 (23rd May 2018) - Ghazi Sherbaf, Farzaneh; Same, Kaveh; Ashraf-Ganjouei, Amir; Aarabi, Mohammad H.
Abstract : In the context of growing evidence supporting disturbed neural connectivity in the pathogenesis of depressive symptoms, we used the diffusion tensor imaging technique to investigate white matter disruptions in previously undiagnosed and hence treatment-naive young adults with mild and moderate depressive symptoms screened by Beck's Depression Inventory test compared with age-matched and sex-matched healthy controls. This is the first diffusion tensor imaging study to assess minor forms of depression. We hypothesized that subthreshold depressive symptoms share the same neural disruptions as major depressive disorder (MDD). Each group included 47 participants with a mean age of 20.1±1.1 years. The exploratory region of interest method was used to assess integrity (fractional anisotropy and mean diffusivity) in 48 regions of the brain based on Mori atlas. Data were recruited from the Southwest University Longitudinal Imaging Multimodal Brain Data Repository. The following pathways showed significant microstructural changes by means of reduced fractional anisotropy in the group with depressive symptoms compared with normal participants: pontine crossing tract; genu of the corpus callosum; posterior limb of the internal capsule (bilaterally); and anterior, posterior, and superior corona radiata (bilaterally). None of the above regions, but the middle cerebellar peduncle and the right superior fronto-occipital fasciculus were shown to differ significantly in the mean diffusivity values between the two groups. On the basis of the current results, our findings provide evidence that the white matter impairments in the interhemispheric connections and frontal–subcortical neural circuits may play a key role in the pathogenesis of depression in young adults. The similarity of neural underpinnings in MDD and minor depressive disorder in this study further proves that these two mood disorders exist in a continuum, and milder depressive symptoms can herald a major episode. Besides the high prevalence and great burden of subthreshold forms of depression on personal and social aspects of life, there is lack of knowledge of them and most studies have mainly focused on MDD. This study provides a new avenue in addressing neuropathology of depression, mainly in subtle forms that are almost always overlooked.